The Effectiveness of Group Guidance Services Using Homeroom Technique to Enhance Students' Self-Esteem - Harahap, Dody Hidayat; Putri Harahap, Ade Chita (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Self-esteem is an evaluation conducted by an individual, particularly the tendency to pay attention to oneself according to the mentality of acceptance or rejection, which indicates the level of an individual's confidence in their abilities, interests, achievements, and worth. Group guidance services function to enable individuals to plan for themselves, decide their own direction, and foster a mentality and perspective to live freely without depending on others. This study aims to determine the feasibility of group guidance services utilizing homeroom techniques to enhance students' self-esteem. The research method used is quantitative experimental with a one-group pretest-posttest design. The population in this study consisted of all tenth-grade students at SMA Negeri 7 Medan, totaling 159 individuals, with a sample of 8 students who had low self-esteem. The sample was taken using purposive sampling techniques. Data analysis was performed using the Wilcoxon test with a significance value of asyimp.sig (2-tailed) 0.012 < 0.05, meaning Ha is accepted. Therefore, it can be concluded that group guidance services with homeroom techniques are effective in increasing students' self-esteem.